The first intron of ARF7 is required for expression in root tips - Jingyi Han; Thomas Welch; Ute Voß; Teva Vernoux; Rahul Bhosale; Anthony Bishopp (iScience, 2024)
Summary: Auxin regulates plant growth and development through the transcription factors of the AUXIN RESPONSE FACTOR (ARF) gene family. ARF7 is one of five activators that bind DNA and elicit downstream transcriptional responses. In roots, ARF7 regulates growth, gravitropism and redundantly with ARF19, lateral root organogenesis. In this study we analyzed ARF7 cis-regulation, using different non-coding sequences of the ARF7 locus to drive GFP. We show that constructs containing the first intron led to increased signal in the root tip. Although bioinformatics analyses predicted several transcription factor binding sites in the first intron, we were unable to significantly alter expression of GFP in the root by mutating these. We instead observed the intronic sequences needed to be present within the transcribed sequences to drive expression in the root meristem. These data support a mechanism by which intron-mediated enhancement regulates the tissue specific expression of ARF7 in the root meristem.